Healthcare-associated infections (HAI) research in Asian countries: a bibliometric analysis - . cahyadin; Ahmad Watsiq Maula; Anis Fuad (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2018)
Health care-associated infections (HAI) are the most frequent adverse event in health-care delivery worldwide, including in Asian countries. Asian countries produced 4,819 HAI publications. Majority of the publications (68%) appeared in the last decade. The average annual growth rate was 14.8%. Japan was the most productive country that contributes about 13.5% of total publications, followed by China (11.7%), and Taiwan (11.6%). Asian HAI research were cited in 76,737 articles with an average of 15.9 citations per publication. The top two most highly cited articles were published in the New England Journal of Medicine followed by the Journal of Clinical Microbiology. The top three productive journals were Journal of Hospital Infection (309 papers; 6.4%), American Journal of Infection Control (198 papers; 4.1%) and Infection Control and Hospital Epidemiology (170 papers; 3.5%). The ten top journals contained 25% of the HAI literatures. Emerging research topics in the last years include ventilator-associated pneumonia, MRSA (methicillin-resistant staphylococcus aureus), acinetobacter baumannii, carbapenems, Republic Korea and tertiary care center.